Translation Accuracy of English Idiomatic Expression into Indonesian in “Big Hero 6” Film Subtitle by Lebah Ganteng - Fitri Iskandar (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2016)
Abstract This article discusses about the types of idiomatic expression and the translation accuracy of English idiomatic expression into Indonesian in “Big Hero 6” film subtitle translated by Lebah Ganteng by using qualitative descriptive method. The writer analyses the data by classifying the type of idiomatic expressions based on McCarthy and O’Dell’s theory about the types of idiom, giving explication toward the translation strategy of idiomatic expression that is done by the translator based on Mona Baker’s theory about translation strategy of idiom, and analyzing the translation accuracy of English idiomatic expression translation into Indonesian considering the appropriate of the context of film and related theory about accuracy-rating assessment by Nababan. As the result, the types of idiomatic expression applied in that film are compound, verb +object, prepositional phrase, and whole clause and sentence. The translator seems prefer to use omission of entire idiom, paraphrasing, and using idiom of similar meaning and form strategy in translating idiom expression. —Abstrak Tulisan ini membahas tentang jenis-jenis ungkapan idiom dan keakurasian terjemahan subtitle idiom dari bahasa Inggris ke dalam bahasa Indonesia dalam film “Big Hero 6” yang diterjemahkan oleh tim Lebah Ganteng dengan menggunakan metode deskriptif. Penulis mengklasifikasi jenis ungkapan idiom berdasrkan teori McCarthy dan O’Dell, mengenai jenis-jenis idiom, dengan memberikan eksplikasi terhadap strategi penerjemahan yang dilakukan berdasarkan teorinya Mona Baker, Strategi Penerjemahan Idiom. Di samping itu penulis juga menganalisis keakurasian penerjemahan ungkapan idiom dari bahasa Inggris ke dalam bahasa Indonesia dengan menggunakan konsep Penilaian Penerjemahan yang diajukan oleh Nababan. Hasil dari pembahasan tentang penerjemahan idiom yang ada dalam film tersebut, penulis menyimpulkan bahwa penerjemah tampaknya lebih sering menggunakan penghilangan idiom, memparafrasa, dan menggunakan kesamaan idiom antara bahasa sumber dan bahasa sasaran. DOI : 10.5281/zenodo.556810